Understanding the Hunga hydration in the context of an underlying stratospheric moistening trend ... - Valle, Luis Millan (Root, 2024)
The 2022 Hunga eruption caused unprecedented stratospheric hydration. Aura Microwave17 Limb Sounder (MLS) measurements show that the stratospheric water vapor mass re-18 mains essentially unchanged as of early 2024 and that the Hunga hydration occurred atop19 a strong (possibly accelerating) moistening trend in the stratosphere. Enhanced by the20 excess Hunga water vapor, dehydration via polar stratospheric cloud (PSC) sedimenta-21 tion in the 2023 Antarctic vortex exceeded climatological values by ∼50%. Simple pro-22 jections, based solely on Antarctic dehydration, illustrate that the timing of the return23 to humidity levels that would have been expected absent the Hunga hydration depends24 on the ongoing stratospheric water vapor trend. For strong moistening, the influx of wa-25 ter entering the stratosphere could offset the enhanced PSC dehydration, resulting in a26 new, more humid ‘equilibrium’ stratospheric state. With the Hunga hydration compound-27 ing an underlying moistening trend, the stratosphere ...